EFFECT OF RBI MONETARY POLICY ON STOCK MARKET- WITH A SPECIAL REFERENCE TO NATIONAL STOCK EXCHANGE - N. Moses; M. Yugandharudu; P. Suchitra (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The Reserve Bank of India (RBI), as the central bank of the country, plays a crucial role in shaping India’s monetary policy. Its periodic policy announcements—especially changes in repo rates, reverse repo rates, and other monetary tools—serve as key indicators of the nation’s economic direction. These announcements significantly influence investor sentiment and often lead to immediate and notable reactions in the stock markets. Stock market participants closely monitor these announcements for signals on inflation control, economic growth, and liquidity conditions. A hike in interest rates is typically viewed as a tightening measure that could slow down borrowing and spending, often leading to a bearish market response. Conversely, rate cuts or accommodative stances are generally perceived as growth-supportive, potentially triggering bullish movements. Analyzing the stock market’s response to RBI’s monetary policy provides valuable insights into investor behavior, sectoral sensitivities (like banking, real estate, and auto), and the overall economic outlook. It also helps investors and policymakers assess the effectiveness and communication of monetary policy decisions. This study aims to explore the short-term and long-term effects of RBI’s monetary policy announcements on the NSE, examining both overall market indices and specific sectoral performances. It will also assess the role of market expectations, surprise elements, and the credibility of RBI communication in influencing stock market reactions.